Makna Mudharab : Suatu Pendekatan Tafsir Maudhu’i - Suprihatin . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2012)
This research theme is the meaning mudharabah: a thematic (maudhu’i) interpretation approach. From this study it can be concluded that the cooperation between shahibul mall and mudharib to carry out the work that generates a profit and the profit sharing provision of clear and definite, while capital losses are borne entirely by shahibul mall. The interpretation of Mudhorobah commentary refers to the Surah of al-Muzammil verse 20 is reinforced by the verses of the Holy Qur’an and the hadith explains the other: (1) That the carrying out mudharabah is permissible in Islam and has a core value of quality equal to jihad (2) The Surat al-Muzammil verse 20 which discusses the absurd with the letter mudharabah in Surah al-Jum'ah verse 10 and the Surah of al-Baqarah verse 198 the suitability thematic (maudhu’i) 'the ability to earn a living and an explanation of the need to make a living without neglecting prayer and worship Hajj, (3) Surat al-Muzammil verse 20 also has relevance to the Surah al-Nisa verse 29 that prohibits making a living in a false way. Among the forms of living in a false way it was an act ghasab, usury and trading urbun. Application of the concept has been applied mudharabah in Islamic banks using the system for results between banks and customers in an effort to avoid usury element contained in the bank rate